Interrelationship between rheumatoid arthritis and diabetes mellitus: current insights and perspectives - Sigedar, Prakash; Giri, Purushottam (International Journal of Research in Medical Sciences, 2026)
Rheumatoid arthritis (RA) and diabetes mellitus (DM) are chronic, systemic conditions with significant global health burdens. Emerging evidence suggests a bidirectional relationship between these diseases, with shared pathophysiological mechanisms, including chronic inflammation, immune dysregulation, and metabolic disturbances. This review explores the current insights into the interrelationship between RA and DM, emphasizing the role of pro-inflammatory cytokines, insulin resistance, and genetic predispositions. Additionally, it examines the impact of therapeutic interventions for RA on glycemic control and vice versa, highlighting challenges and opportunities in clinical management. Understanding these interactions is crucial for developing integrated treatment strategies, improving patient outcomes, and addressing the broader implications of coexisting RA and DM. This review article aims to provide a comprehensive perspective on the evolving knowledge in this field and to identify areas for future research.